The Effect of Capital Adequacy Ratio, Loan to Deposit Ratio and Return on Assets on Stock Prices At PT. Bank Central Asia Tbk Period 2011-2020 - Jamaluddin Jamaluddin (International Journal of Education, Information Technology, and Others, 2022)
This study aims to determine how the effect of Capital Adequacy Ratio, Loan To Deposit Ratio and Return On Assets on Stock Prices at PT. Bank Central Asia Tbk Period 2011-2020. The research method used is a descriptive method with a quantitative approach. The population in this study is the financial statements of PT Bank Central Asia, Tbk. The data method used in this research is multiple linear regression analysis, classical assumption test which includes normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. Significant tests include the t-test and f-test, as well as the correlation coefficient and the coefficient of determination at a significance level of 5%. The data were processed and analyzed using the SPSS version 25 application program. The results of this study indicate that partially the Capital Adequacy Ratio has a significant effect on stock prices, with a value of Tcount 5.043 > Ttable 1.943 with a significant value of 0.002 <0.05. Partially, Loan to Deposit Ratio has no significant effect on stock prices, with a value of Tcount (0.249) < Ttable 1.943 with a significant value of 0.812 > 0.05. Partially Return On Assets has no significant effect on stock prices, with a value with Tcount (0.252) < Ttable 1.943 with a significant value of 0.809 > 0.05. Simultaneously, the Capital Adequacy Ratio, Loan to Deposit Ratio and Return On Assets have a significant effect on stock prices, with a value with Fcount 11.137 > Ftable 4.35 with a significance of 0.007 < 0.05.